Zindagi phir muskurai - Meena (Unicef Lahore, 2012)
Zindagi Phir Muskurai likely refers to a hopeful and uplifting theme, often associated with overcoming adversity or finding joy in life. This theme is commonly found in children's literature, particularly those produced by UNICEF. UNICEF, in collaboration with authors like Meena, creates stories that aim to educate and inspire young readers. These stories often tackle important social issues, such as child rights, health, and education, while also providing entertainment and positive messages.